Mass Spectrometry-based Serum Proteomics for Biomarker discovery and validation - Santosh D. Bhosale; Robert Moulder; Petri Kouvonen; Riitta Lahesmaa; David R. Goodlett (Springer, 2022)
Blood protein measurements are used frequently in the clinic in the assessment of patient health. Nevertheless, there remains the need for new biomarkers with better diagnostic specificities. With the advent of improved technology for bioanalysis and the growth of biobanks including collections from specific disease-risk cohorts, the plasma proteome has remained a target of proteomics research towards the characterization of disease related biomarkers. The following protocol presents a workflow for serum/plasma proteomics including details of sample preparation both with and without immunoaffinity depletion of the most abundant plasma proteins, and methodology for selected reaction monitoring mass spectrometry validation.
Serum/plasma proteomics : Methods and Protocols